Seismic vulnerability and loading capacity of a wire strained bridge based on structural reliability - Muñoz, Edgar; Núñez, Federico; Rodríguez, Jorge A.; Ramos, Alfonso; Otálora, Camilo (Revista Ingeniería de Construcción, 2010)
This document presents the analysis of seismic vulnerability and load capacity for Cesar Gaviria Trujilo Viaduct, by means of structural reliability techniques based on instrumentation works. Such study includes: geophysical trial tests, trials tests on material mechanical properties, environmental vibrations, measurements on the effects of traffic load, wireless instrumentation, loading tests, wire strainers tensile strength, etc. Additionally, the study explains structural models on finite elements, which were developed for the bridge, as well as its calibration process based on the loading test, and dynamical properties determined on experimental basis. Furthermore, the study indicates the way stress records collection of all structural elements was conducted, during the construction process, in accordance with the job site log-book. As for reliability, a seismic threat analysis was made as well as dynamic responses on the bridge site, where nine spectrums were obtained at different return periods. By studying strength probability curves and seismic loads of pylons, it was found they have reliability indexes in accordance with recommendations by the international regulations. However, one of the superstructure’s elements, which were introduced to evaluate its capacity on traffic effects, has a reliability index far higher than the ranges recommended by international regulations. Finally, some wire strainers have higher level tensions than specifications admitted during its design and international recommendations for these kinds of bridges.